AN EXPERIENTIAL LEARNING MODEL TO ENHANCE THE METACOGNITIVE ABILITIES OF PRE-SERVICE TEACHERS - Panut Setiono; Punaji Setyosari; Henry Praherdhiono; Titik Harsiati; Yuli Amaliyah (Program Studi PGSD Universitas Flores, 2025)
Social education programs often face challenges in effectively developing metacognitive skills in pre-service teachers, which are crucial for enhancing problem-solving and decision-making abilities in the classroom. Metacognition allows teachers to monitor and regulate their thinking, yet many teacher education programs lack structured frameworks to support this development. This study aims to address this gap by developing an Experiential Learning (EL) model designed to enhance the metacognitive skills of pre-service social education teachers. Based on Meijer et al.'s (2013) framework, the model integrates three core components: metacognitive knowledge, metacognitive regulation, and metacognitive responsiveness. A qualitative research design was employed, using expert validation through the Item-Objective Congruence (IOC) method and a Likert-scale suitability assessment. Five education experts evaluated the model’s alignment with metacognitive competencies, yielding a high suitability score of 4.56 out of 5. The model follows a learning cycle that incorporates concrete experience, reflective observation, abstract conceptualization, and active experimentation. The results indicate that integrating metacognitive strategies into learning activities, with clearly defined instructor roles, significantly enhances pre-service teachers' metacognitive abilities. This research emphasizes the importance of incorporating reflective, contextual learning designs to foster higher-order thinking skills within teacher education, particularly in the underdeveloped field of social education.